Heterogeneous nanostructure developed in heavily cold-rolled stainless steels and the specific mechanical properties. (May 2017) - Miura, H.; Kobayashi, M.; Todaka, Y.; Watanabe, C.; Aoyagi, Y.; Sugiura, N.; Yoshinaga, N.
Abstract: Stainless steels were cold rolled to 92% reduction. The microstructure developed in a stable austenitic stainless steel was complicated heterogeneous nanostructure composed of lamellar-twin domains, shear bands and low-angle lamellar boundaries. Cold-rolled duplex stainless steel, however, exhibited more complicated and mixed microstructure where ferritic lamellar and the heterogeneous nanostructure of austenite were alternatively stacked. The heavily cold-rolled stainless steels followed by ageing exhibited marvelous high tensile strength over 2.6 GPa perpendicular to the rolling direction, although around 2 GPa along the rolling direction. Even while such high strength, moderate plastic elongation over 5% was attained. Graphical abstract: